In Vivo : a perspective on consciousness through interdisciplinary collaboration in an age of man, nature and technology - Tan, Jun Kang (Nanyang Technological University, 2020)
Can a living entity without a voice and mobility communicate with the aid of technology? In Vivo​ is an interactive art installation that delves into the artistic visualisation of the internal physiological activity of a bonsai plant through the use of magnetic resonance imaging (MRI), projection mapping and analogue-digital interfaces. Inspired by the ability of MRI technology to detect internal responsiveness in comatose patients, the work capitalises on the imaging capabilities of this technique to visualise the internal states of the plant. In Vivo​ begins by speculating what consciousness means to plants through observation, exploring the possibility of a plant—which neither speaks nor moves—“expressing itself” via self-images controlled by its own physiological dynamics. The work provides a platform to imagine what advances in medical imaging technology can achieve, stretching its potential beyond its typical biomedical uses and extending it to other areas of research. Through the use of three MRI image sets, one impaired by artefact, a baseline control and a final three-dimensional reconstruction; the models are visually present in digital and physical space, creating an experiential installation that aims to give voice to otherwise voiceless living entities. By using man made technology on plants, the work plans to approach and understand consciousness in plants as a methodology to understand human consciousness.